Store gæstespil hos en lille virksomhed: Historien om Theatre Traffic of Scandinavia - Jarl, Stig (Peripeti, 2022)
Large guest performances featured by a small company. The story of Theatre Traffic In 1976 Per Moth formed the small company Theater Traffic of Scandinavia, which until the early 1990s imported several smaller and larger guest performances, some of which attracted great attention in Denmark. Based on archives of the company, Stig Jarl, who was member of the board and worked with Theatre Traffic for a period, sheds light on the conditions for this kind of enterprise. The article also describes the special terms on which Theatre Traffic collaborated with Østre Gasværk, where many of the productions were shown.